The Bad Guys in Do-you-think-he-saurus? - Blabey, Aaron (Blabey, Aaron. Bad guys, 2018)
The Bad Guys find themselves sixty-five million years in the past where they must avoid being eaten by dinosaurs, fix their broken time machine, and get back home before an evil alien destroys the world.